Implementing the Independent Curriculum to Develop Twenty-First Century Competencies in Indonesian Senior Secondary Schools - Nova Alfatih Raya; Syamsul Hadi; Rika Afdalia Nur (Gema Cendekia Institute, 2025)
The implementation of the Independent Curriculum (Kurikulum Merdeka) represents a major shift in Indonesian education toward competency-based and student-centered learning aimed at addressing the demands of the twenty-first century. This study investigates how the Independent Curriculum is implemented in Indonesian senior secondary schools and examines its role in developing students’ twenty-first century competencies, including critical thinking, creativity, collaboration, communication, information literacy, and character development aligned with the Pancasila Student Profile. Employing a mixed-methods explanatory design, the study integrates quantitative data from student and teacher questionnaires with qualitative data obtained through interviews and document analysis. The findings reveal that the Independent Curriculum has been partially but progressively implemented, with notable variation across schools and subjects. When effectively enacted through deep learning and project-based learning approaches, the curriculum contributes positively to students’ cognitive, social, and creative competencies. Project-Based Learning emerges as a key pedagogical strategy supporting collaborative learning and authentic problem-solving, while P5 projects strengthen the integration of national values within competency development. However, the study also identifies persistent challenges related to teacher readiness, assessment literacy, curriculum interpretation, and institutional support. These factors significantly influence the consistency and quality of curriculum implementation. Overall, the results indicate that the Independent Curriculum holds substantial potential to enhance twenty-first century competencies in senior secondary education, provided it is supported by sustained professional development, clear implementation guidance, and strong school leadership. The study contributes empirical evidence to curriculum reform discourse and offers insights for policymakers and educators seeking to strengthen competency-oriented learning in Indonesian secondary schools.